Implementasi Metode Pembelajaran Kooperatif Model Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Mata Pelajaran Fisika Siswa Kelas X SMA Negeri 1 Rambah Hilir - Asra, Azmi (Universitas Pasir Pengaraian, 2012)
Model Numbered Head Together (NHT) is a cooperativelearning model that is designed to influence the patterns ofstudent interaction. By using this learning model will involveall members of the group and is a good way to instill a positiveattitude interdependence and individual responsibility are highthat students will learn seriously, understand and comprehendthe material being studied, and ultimately have an impact onimproving student learning outcomes . To the authors areinterested in doing research to take the title